Plan estratégico de mercadeo para la captación de nuevos estudiantes en el Instituto Poliandino de la ciudad de Bogotá (2021)
This work is a strategic marketing plan which is created to attract new students for Poliandino Institute of Bogotá, this type of marketing is innovative from it seeks that companies grow through advertising that is carried out by the most used social networks. On these apps potential students could be found who are in the age range and want to learn different courses that the Poliandino institute offers, such as courses in English, gastronomy, mechanics and DJ.